Visual codon: a user-friendly Python program for viewing and optimizing gene GC content - Shiming Lin; Fei Xu; Bifang Huang; Li-li Zhao; Danni Pan; Shiqiang Lin (PeerJ)
Due to the codon bias of different species, codon optimization is usually carried out in the process of heterologous protein expression. At present, there are a variety of codon optimization tools. However, the optimized sequences may still have high or low points of local guanine and cytosine (GC) content, which is not conducive to the primer design of gene subcloning, and also makes it difficult to perform the experiment of synthesizing the whole gene with DNA fragments by polymerase chain reaction (PCR) reaction. In this study, we present a stand-alone software written in Python, with which users can manually check and adjust the GC content of sequence-optimized genes. The software takes the codon frequency of Escherichia coli as default and can work with other species as well. It provides a Graphical User Interface (GUI) interface, which allows users to change codons and intuitively see the effect of codon changes on local GC content. Our program brings convenience for the optimization of gene GC content and the subsequent gene cloning experiments.